Motor and neurocognitive profiles of children with symptomatic spinal muscular atrophy type 1 with two copies of SMN2 before and after treatment: a longitudinal observational study - Bitetti, Ilaria; Manna, Maria Rosaria; Stella, Roberto; Varone, Antonio (Frontiers in Neurology, 2024)
Spinal muscular atrophy (SMA) is a neurodegenerative disease caused by mutations in the survival motor neuron 1 (SMN1) gene. In clinical studies, gene replacement therapy with onasemnogene abeparvovec (formerly AVXS-101, Zolgensma®, Novartis) was efficacious in improving motor functioning in children with SMA. However, its effects on cognitive and language skills are largely unknown. This longitudinal observational study evaluated changes in motor and neurocognitive functioning over a 1-year period after administration of onasemnogene abeparvovec in 12 symptomatic SMA type 1 patients with two copies of SMN2 aged 1.7-52.6 months at administration. Motor functioning was measured using the Children's Hospital of Philadelphia Infant Test for Neuromuscular Disorders (CHOP-INTEND) while neurocognitive assessment was measured using Griffiths III. Motor milestones and language ability were also assessed at each timepoint. Statistically significant increases in median CHOP-INTEND scores from baseline were observed at 1, 3, 6, and 12 months after onasemnogene abeparvovec administration (all p ≤ 0.005). Most (91.7%) patients were able to roll over or sit independently for >1 minute at 12 months. Significant increases in the Griffiths III Foundations of Learning, Language and Communication, Eye and Hand Coordination, and Personal-Social-Emotional subscale scores were observed at 12-months, but not in the Gross Motor subscale. Speech and language abilities progressed in most patients. Overall, most patients showed some improvement in cognitive and communication performance after treatment with onasemnogene abeparvovec in addition to significant improvement in motor functioning and motor milestones. Evaluation of neurocognitive function should be considered when assessing the global functioning of patients with SMA.